“Ser homem é respeitar para ser respeitado”: os sentidos da guerra, respeito e masculinidades entre jovens em cumprimento de medidas socioeducativas em meio aberto - Oliveira, João Victor Borri de (2025)
The studies that have linked masculinities and criminality for a long time adopted an approach centered on violence. This dissertation discusses the masculinities of young men who were serving open-environment socio-educational measures at an institution called “Associação Caminhos Abertos” interior of São Paulo. However, the connection between crime and masculinities in this context does not occur through the path of violence. Furthermore, the academic agenda to which I contribute has not seen much continuity within Sociology. As a result, there are few studies that consider crime in relation to sexuality and gender approaches and, consequently, masculinities. Thus, this dissertation presents itself as a contribution to fill that gap. My argument in this text is that these young men live in a constant war in pursuit of respect. The term “war” appears here as an analytical category that gives meaning to the wide variety of everyday conflicts these young people experience while seeking respect. In this way, the pursuit of respect becomes one of the lenses through which we can interpret their daily lives. This respect, as I demonstrate in the first chapter, has both material and symbolic dimensions, which are always interconnected. The material aspect involves what is tangible and present in everyday life, such as brand-name clothing, sneakers, luxury items, or accessories. The symbolic aspect refers to the social and emotional meanings associated with these elements. The value of something, therefore, lies not only in the object itself but in what it communicates or represents. These dimensions are always connected: in the experience of these young men, material objects carry symbolic meanings, and symbolic aspects are often anchored in material elements. In the second chapter, I argue that the world of crime (or the “vida loka”) constitutes one of the possible arenas for earning respect. Crime appears not only as a means of generating income but also as a source of belonging. This dynamic intensifies when we understand involvement in crime as a form of child labor or a way of making a living. Finally, in the third chapter, I show that crime and its code of conduct—o proceder—operate as a normative regime that spreads into other spaces. This allows us to observe the logic of the pursuit of respect across various other arenas of these young men’s social lives.